Evaluation of Local Intra-Arterial Fibrinolytic Therapy for Acute Middle Cerebral Artery Occlusion - Tamatani, S. (Centauro S.r.l., 2000)
Fibrinolytic therapy for acute ischaemic stroke has been investigated in several clinical trials, with various protocols. This retrospective study was undertaken to evaluate the efficacy and limitation of local intra-arterial fibrinolytic therapy using urokinase (UK) in patients with acute middle cerebral artery occlusion. Fifty patients were treated with local intra-arterial fibrinolytic therapy within six hours after onset of symptoms. The median National Institutes of Health Stroke Scale (NIHSS) score was 17 (range, 6 to 28). Two hundred and forty thousand IU of UK was administered through a microcatheter for 20 minutes. When arterial recanalization was not achieved, a second or third infusion was performed. Maximum dosage of UK was 0.96 × 106 IU. Recanalization efficacy was evaluated at the end of fibrinolytic therapy and intracranial haemorrhage was assessed within 24 hours. Clinical outcome was evaluated three months after ictus with modified Rankin scale (RS). Thirty-nine patients (78%) obtained recanalization. Twenty-nine of 39 (74%) showed clinical improvement just after treatment. On the other hand, only 18% patients (2/11) who did not recanalize demonstrated improvement. Twenty-five of 50 (50%) patients recovered to RS score 0 or 1, however; only 28% of patients (5/18) with proximal Ml occlusion obtained good outcome and 39% of them (7/18) died. The mean time interval from onset to treatment did not affect outcome. The overall incidence of haemorrhagic event (HE) within 24 hours was 36%, however; 78% of patients with proximal Ml occlusion showed HE. Only one patient with HE clinically deteriorated. In conclusion, local intra-arterial fibrinolytic therapy could be a safe and effective method for acute middle cerebral artery occlusion, however; indication of this therapy for patients with proximal Ml occlusion should be carefully decided.